2019
DOI: 10.5812/ans.12446
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology and Antimicrobial Sensitivity of Isolated Bacteria from Pressure Ulcers After Spinal Cord Injury

Abstract: Background: Infection is a common problem in chronically denuded skin, especially in pressure ulcers (PUs). It is one of the main reasons for delayed wound healing, in addition to morbidity and even mortality after spinal cord injury (SCI). Objectives:The current study aimed at determining the pathogenic microorganisms, as well as their antimicrobial sensitivity, isolated from active PUs in post-rehabilitated cases with SCI. Methods:The current cross sectional study was conducted from January 2015 to January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“… 35 Pressure ulcer risk assessment tools are varied and inconsistent in their inclusion of different risk factors, 36 an issue that has prompted substantial research into their reliability and validity. 37 , 38 , 39 , 40 The Braden Scale was selected as it has been shown to have moderate to high validity and reliability among varied patient cohorts including trauma/ICU patients, 40 , 41 , 42 paediatric patients, 43 , 44 long term care patients, 45 , 46 patients with spinal cord injuries, 47 and elderly patients. 48 The inter‐rater reliability of the Braden Scale was substantial in every ward versus not good in orthopaedic and spinal surgery wards for the Norton Scale and not good in the orthopaedic wards for the Waterlow Scale.…”
Section: Methodsmentioning
confidence: 99%
“… 35 Pressure ulcer risk assessment tools are varied and inconsistent in their inclusion of different risk factors, 36 an issue that has prompted substantial research into their reliability and validity. 37 , 38 , 39 , 40 The Braden Scale was selected as it has been shown to have moderate to high validity and reliability among varied patient cohorts including trauma/ICU patients, 40 , 41 , 42 paediatric patients, 43 , 44 long term care patients, 45 , 46 patients with spinal cord injuries, 47 and elderly patients. 48 The inter‐rater reliability of the Braden Scale was substantial in every ward versus not good in orthopaedic and spinal surgery wards for the Norton Scale and not good in the orthopaedic wards for the Waterlow Scale.…”
Section: Methodsmentioning
confidence: 99%
“…19 Some common characteristics and symptoms of this stage of PUs (redness, pain, heat and swelling) indicate the high proliferation of several species of pathogenic agents and communities. 104 The characteristics of pathogenic agents in these PU stages are similar to those in stages II and IV, despite the increase in complexity 105,106 . In a study aimed at investigating the association between the bacterial bioburden and the presence of wound inflammation, the authors found that unstageable and deep tissue PU stages are reservoirs of high bacterial counts and positive biofilm formation.…”
Section: Evidence Of Pu Stages and Infectious Complicationsmentioning
confidence: 93%